Using of TLR2 and TLR4 as Biomarker for Detection the Severity of Sepsis - Younis , Farah Qahtan; Alwan, Ali Hussien; Zaki, Neihaya Hekmit (International Journal of Psychosocial Rehabilitation, 2020)
Our study has been aimed to find the relation between the expression of toll-like receptors 2, 4, level of TNF-α, IL-10 and soluble HLA-DR with the severity bacterial septic syndrome in Iraqi patients. The quantitative real-time PCR technique has been used for measure TLR2 and TLR4 gene expression in whole blood, and ELISA technique has been used for detection of cytokines TNF-α, IL-10 and soluble HLA-DR from 75 septic syndrome cases (nineteen of patients showed symptoms of systemic inflammatory response syndrome (SIRS); twenty eight patients have sepsis, seventeen patients suffered from severe sepsis and eleven patients have septic shock) and 55 healthy controls (HC). TLR2 and TLR4 mRNA expression were higher significantly in the all patients (P< 0.05), TNF-α, IL-10 and sHLA-DR serum levels were significantly elevated in the serum of patients with septic syndrome compared with controls (P